PBAT-PLA copolyester and preparation method thereof

By copolymerizing prepolymers with prepolymers PBAT and PLA under high vacuum conditions, the problem of incompatibility between PBAT and PLA is solved, and an environmentally friendly and non-toxic synthesis process and high-performance PBAT-PLA copolyester are realized, improving the compatibility and mechanical properties of composite materials.

CN119591852APending Publication Date: 2025-03-11CHINA CHEM DONGHUA TIANYE NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411838217.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

It is difficult for PBAT and PLA to be fully mixed and dispersed, resulting in differences in product performance, and existing chain extenders are toxic and cost-effective, limiting their application scope.

Method used

By copolymerizing with prepolymers PBAT and PLA under high vacuum conditions, the use of toxic chain extenders and solvents is avoided, and an environmentally friendly and non-toxic synthesis process is achieved, and the molecular weight of the copolyester is controlled by precise control of the vacuum degree and temperature.

Benefits of technology

The problem of difficulty in compatibility between PBAT and PLA was successfully solved, and PBAT-PLA copolyester with a weight average molecular weight of 100,000-150,000 was obtained, which improved the compatibility and mechanical properties of the composite material, and was simple in process, low in cost and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591852A_ABST
    Figure CN119591852A_ABST
Patent Text Reader

Abstract

The invention relates to a PBAT-PLA copolyester and a preparation method thereof. The preparation method of the PBAT-PLA copolyester comprises the following steps: preparing a PBAT copolyester oligomer: mixing terephthalic acid, adipic acid, 1, 4-butanediol and a catalyst 1, and carrying out esterification reaction to obtain a PBAT co-ester; and carrying out a pre-polycondensation reaction on the PBAT co-ester to obtain a PBAT prepolymer, namely the PBAT copolyester oligomer, preparing a PLA resin oligomer: mixing lactic acid with a catalyst 2, and carrying out esterification reaction to obtain a PLA ester; the PLA ester is subjected to a pre-polycondensation reaction, and a PLA prepolymer, namely the PLA resin oligomer, is obtained; and preparing a final polymer: carrying out melt blending on the PBAT prepolymer and the PLA prepolymer, adding a catalyst 3, and carrying out condensation polymerization to obtain the PBAT-PLA final polymer, namely the PBAT-PLA copolyester. According to the PBAT-PLA copolyester and the preparation method thereof, the preparation method is green, environment-friendly, low in cost and simple, and the problem that PBAT and PLA are difficult to be compatible is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester synthesis, and specifically relates to a PBAT-PLA copolyester and a preparation method thereof. Background Art

[0002] PBAT resin is a copolymer of butylene adipate and butylene terephthalate, which has the characteristics of PBA and PBT. It has good ductility and elongation at break, as well as good heat resistance and impact resistance. In addition, it has excellent biodegradability. It is one of the most active biodegradable materials in the current research of biodegradable plastics and has the best market application. It is widely used in many processing fields such as agricultural mulch. However, PBAT resin also has some performance deficiencies, such as insufficient mechanical strength and susceptibility to impact and pressure, which limits its practical application in certain applications; poor thermal stability, easy to degrade and decompose at high temperatures; poor water resistance, high permeability to water, and easy to absorb water. This makes it prone to hydrolysis and degradation in humid environments, affecting its service life and performance;

[0003] Polylactic acid (PLA) is a polymer biomaterial chemically synthesized from lactic acid (LA). It is non-toxic, biodegradable, and has good biocompatibility. Its final degradation products are H20 and C02, which will not cause environmental pollution. The intermediate product lactic acid is also a normal sugar metabolism product of the human body, with good biodegradability and compatibility; its performance is better than existing plastic materials such as polyethylene, polypropylene, and polystyrene. In the medical field, polylactic acid is widely used in drug controlled release carriers, tissue engineering scaffolds, internal fixation materials, surgical sutures, artificial skin, medical implants, tissue engineering, orthopedic equipment, drug release systems, etc. because its final degradation products are carbon dioxide and water, which are non-irritating to the human body and have excellent biocompatibility and biodegradability. In industrial and agricultural application fields: polylactic acid can be used to manufacture degradable packaging materials, fibers, films, etc. in industry. In agriculture, it can be used to make degradable agricultural films, seedling containers, etc. However, polylactic acid has the disadvantages of low elongation at break, poor impact strength, poor toughness, lack of elasticity and flexibility, and is difficult to meet certain practical requirements, limiting its application. Therefore, it is necessary to toughen polylactic acid, and traditional methods include physical modification and chemical modification.

[0004] Therefore, blending PBAT with PLA can obtain products with better comprehensive performance. The existing mature technology generally adopts PBAT and PLA to directly blend and then add a chain extender with an epoxy structure or a diisocyanate group, and realizes the melt blending of PBAT and PLA resins by twin-screw melt extrusion, which successfully solves the compatibility problem between the two. However, the processing time is short, and it is difficult to truly achieve full mixing, dispersion and compatibility of the two resins, resulting in certain differences in the performance of different positions of the product; in addition, the chain extender containing an epoxy structure is generally expensive, and the chain extender containing a diisocyanate group has a certain toxicity, which makes the blending modification of PBAT and PLA resin not advantageous in terms of cost and environmental protection. Therefore, how to successfully solve the problem of PBAT and PLA being difficult to fully mix, disperse and compatibility through the adjustment of polymerization process and auxiliary agents, and develop a copolyester of PBAT and PLA that has both the performance of PBAT and PLA resins, and is harmless, non-toxic, environmentally friendly and low-cost, has become a new research direction.

[0005] In view of this, the present invention proposes a new PBAT-PLA copolyester and a preparation method thereof, which successfully solves the problem that PBAT and PLA are difficult to fully mix, disperse and be compatible, and has the advantages of being green, environmentally friendly, low cost and simple method. Summary of the invention

[0006] The object of the present invention is to provide a method for preparing PBAT-PLA copolyester, which is green, environmentally friendly, low-cost, simple, and solves the problem of difficult compatibility between PBAT and PLA.

[0007] In order to achieve the above purpose, the technical solution adopted is:

[0008] A method for preparing PBAT-PLA copolyester comprises the following steps:

[0009] Preparation of PBAT copolyester oligomer: terephthalic acid, adipic acid, 1,4-butanediol and catalyst 1 are mixed and subjected to esterification reaction to obtain PBAT coesterification product; the PBAT coesterification product is subjected to pre-polycondensation reaction to obtain PBAT prepolymer, i.e., the PBAT copolyester oligomer;

[0010] Preparation of PLA resin oligomer: Lactic acid and catalyst 2 are mixed and subjected to esterification reaction to obtain PLA ester; the PLA ester is subjected to pre-polycondensation reaction to obtain PLA prepolymer, i.e., the PLA resin oligomer;

[0011] Preparation of final polymer: After the PBAT prepolymer and the PLA prepolymer are melt-blended, catalyst 3 is added to carry out polycondensation reaction to obtain a PBAT-PLA final polymer, namely, the PBAT-PLA copolyester.

[0012] Furthermore, in the preparation of the PBAT copolyester oligomer, the esterification reaction temperature is 225-245° C., the time is 3-5 h, and the pressure is 75-85 kPa;

[0013] The pre-polycondensation reaction temperature is 225-235°C, the time is 2-2.5h, and the pressure is 1-2kpa;

[0014] The molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1:1.5-1.7.

[0015] Furthermore, in the preparation of the PBAT copolyester oligomer, the esterification reaction temperature is 230° C., the time is 4 h, and the pressure is 80 kPa;

[0016] The pre-polycondensation reaction temperature is 235°C, the time is 2h, and the pressure is 1kpa;

[0017] The molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1:1.6, and the molar ratio of terephthalic acid and adipic acid is 48:52.

[0018] Furthermore, in the preparation of PLA resin oligomer, the esterification reaction temperature is 180-190°C, the time is 5-8h, and the pressure is 85-95kpa;

[0019] The pre-polycondensation reaction temperature is 200-220°C, the time is 3-5h, and the pressure is 1-3kpa.

[0020] Furthermore, in the preparation of PLA resin oligomer, the esterification reaction temperature is 185°C, the time is 6h, and the pressure is 90kpa;

[0021] The pre-polycondensation reaction temperature is 210°C, the time is 4 hours, and the pressure is 1 kPa.

[0022] Furthermore, in the preparation of the final polymer, the polycondensation reaction is carried out under nitrogen protection, the polycondensation reaction temperature is 225-235°C, the time is 3-5h, and the pressure is 5-50pa absolute pressure;

[0023] The molar ratio of PBAT prepolymer to PLA prepolymer is 9-1:1.

[0024] Furthermore, in the preparation of the final polymer, the condensation reaction temperature is 235° C., the time is 4 hours, and the pressure is 50 Pa absolute pressure.

[0025] Furthermore, the molar ratio of tetrabutyl titanate to triphenyl phosphate in the catalyst 1 is 6-7:1;

[0026] The catalyst 2 comprises stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 1.5-2.5:1;

[0027] The molar ratio of tetrabutyl titanate to p-toluenesulfonic acid in the catalyst 3 is 3-5:1.

[0028] Furthermore, the molar ratio of tetrabutyl titanate to triphenyl phosphate in the catalyst 1 is 6.4:1;

[0029] The catalyst 2 comprises stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 2:1;

[0030] The molar ratio of tetrabutyl titanate to p-toluenesulfonic acid in the catalyst 3 is 4:1.

[0031] Another object of the present invention is to provide a PBAT-PLA copolyester prepared by the above-mentioned preparation method, with a weight average molecular weight of 100,000-150,000, and PLA and PBAT are fully mixed, dispersed and compatible.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The diisocyanate chain extender used in the existing PBAT-PLA copolymerization synthesis method is toxic, which limits its application scope. The technical solution of the present invention avoids the use of diisocyanate chain extenders by directly using prepolymer PBAT and prepolymer PLA to copolymerize PBAT-PLA copolyester under high vacuum conditions, and does not add any toxic chain extenders or solvents, thereby achieving an environmentally friendly and non-toxic synthesis process.

[0034] 2. Compared with the method of obtaining PBAT-PLA by ring-opening lactide and PBAT, the technical solution of the present invention eliminates the step of purifying lactide, so that the production cost of the present invention is lower.

[0035] 3. The technical solution of the present invention, during the copolymerization synthesis process, by accurately controlling the vacuum degree in the range of 5-50 Pa and reacting in a specific temperature range, can effectively control the molecular weight of the copolyester to obtain PBAT-PLA copolyester with a weight average molecular weight of 100,000-150,000.

[0036] 4. The technical solution of the present invention, the PBAT-PLA composite material obtained by copolymerization, effectively improves the compatibility problem of the PLA / PBAT composite material, and further improves the mechanical properties of the copolyester.

[0037] 5. Compared with the preparation method of the modified PLA-PBAT composite material, the technical solution of the present invention has the advantages of simple process and green and environmentally friendly whole process. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION

[0039] In order to further illustrate a PBAT-PLA copolyester and a preparation method thereof of the present invention and achieve the intended purpose of the invention, the following is a detailed description of a PBAT-PLA copolyester and a preparation method thereof according to the present invention, its specific implementation, structure, characteristics and efficacy, in combination with preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0040] The following will further introduce a PBAT-PLA copolyester and its preparation method of the present invention in detail in conjunction with specific embodiments:

[0041] A PBAT-PLA copolyester and a preparation method thereof described in the present invention is a copolymerization synthesis method of PBAT-PLA copolyester. Prepolymer PBAT and prepolymer PLA are put into a high vacuum polycondensation reactor, and the vacuum degree is controlled to finally obtain a PBAT-PLA copolyester with a weight average molecular weight of 100,000-150,000. Compared with the prior art in which a diisocyanate is used to initiate a chain extension reaction between PLA and PBAT to obtain a polymer, the present invention directly uses prepolymer PBAT and prepolymer PLA to directly copolymerize to synthesize PBAT-PLA copolyester under a vacuum degree of 5-100Pa without adding a chain extender diisocyanate or any other solvent, thereby avoiding the harm of diisocyanates and other solvents to the human body and the environment. Compared with the prior art in which PBAT-PLA is obtained by ring opening of lactide, the present invention has a low production cost. Combined with Figure 1 , the technical solution of the present invention is:

[0042] A method for preparing PBAT-PLA copolyester comprises the following steps:

[0043] Preparation of PBAT copolyester oligomer: terephthalic acid, adipic acid, 1,4-butanediol and catalyst 1 are mixed and subjected to esterification reaction to obtain PBAT coesterification product; the PBAT coesterification product is subjected to pre-polycondensation reaction to obtain PBAT prepolymer, i.e., the PBAT copolyester oligomer;

[0044] Preparation of PLA resin oligomer: Lactic acid and catalyst 2 are mixed and subjected to esterification reaction to obtain PLA ester; the PLA ester is subjected to pre-polycondensation reaction to obtain PLA prepolymer, i.e., the PLA resin oligomer;

[0045] Preparation of final polymer: After the PBAT prepolymer and the PLA prepolymer are melt-blended, catalyst 3 is added to carry out polycondensation reaction to obtain a PBAT-PLA final polymer, namely, the PBAT-PLA copolyester.

[0046] Preferably, in the preparation of the PBAT copolyester oligomer, the esterification reaction temperature is 225-245°C, the time is 3-5h, and the pressure is 75-85kpa;

[0047] The pre-polycondensation reaction temperature is 225-235°C, the time is 2-2.5h, and the pressure is 1-2kpa;

[0048] The molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1:1.5-1.7, that is, the alcohol-acid ratio is 1.5-1.7:1.

[0049] Further preferably, in the preparation of the PBAT copolyester oligomer, the esterification reaction temperature is 230° C., the time is 4 h, and the pressure is 80 kPa;

[0050] The pre-polycondensation reaction temperature is 235°C, the time is 2h, and the pressure is 1kpa;

[0051] The molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1:1.6, and the molar ratio of terephthalic acid and adipic acid is 48:52.

[0052] Preferably, in the preparation of PLA resin oligomer, the esterification reaction temperature is 180-190°C, the time is 5-8h, and the pressure is 85-95kpa;

[0053] The pre-polycondensation reaction temperature is 200-220°C, the time is 3-5h, and the pressure is 1-3kpa.

[0054] Further preferably, in the preparation of the PLA resin oligomer, the esterification reaction temperature is 185° C., the time is 6 h, and the pressure is 90 kPa;

[0055] The pre-polycondensation reaction temperature is 210°C, the time is 4 hours, and the pressure is 1 kPa.

[0056] Preferably, in the preparation of the final polymer, the polycondensation reaction is carried out under nitrogen protection, the polycondensation reaction temperature is 225-235°C, the time is 3-5h, and the pressure is 5-50pa absolute pressure;

[0057] The molar ratio of PBAT prepolymer to PLA prepolymer is 9-1:1.

[0058] Further preferably, in the preparation of the final polymer, the polycondensation reaction temperature is 235° C., the time is 4 h, and the pressure is 50 Pa absolute pressure.

[0059] Preferably, the molar ratio of tetrabutyl titanate to triphenyl phosphate in the catalyst 1 is 6-7:1;

[0060] The catalyst 2 comprises stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 1.5-2.5:1;

[0061] The molar ratio of tetrabutyl titanate to p-toluenesulfonic acid in the catalyst 3 is 3-5:1.

[0062] Further preferably, the molar ratio of tetrabutyl titanate to triphenyl phosphate in the catalyst 1 is 6.4:1;

[0063] The catalyst 2 comprises stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 2:1;

[0064] The molar ratio of tetrabutyl titanate to p-toluenesulfonic acid in the catalyst 3 is 4:1.

[0065] The raw materials not described in detail in this embodiment can be purchased from the market, and the treatments not described in detail adopt mature conventional means in the prior art and are common knowledge in the art.

[0066] Example 1.

[0067] The specific steps are as follows:

[0068] (1) Preparation of PBAT oligomers:

[0069] 3.415kg of purified terephthalic acid, 3.25kg of adipic acid, 6.17kg of 1,4-butanediol, and 18g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 6.4:1) were accurately weighed and added to reactor I for esterification reaction. The esterification reactor was heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 230°C. The stirring speed of the reactor was gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure was gradually pumped from normal pressure to vacuum 80kpa. The esterification reaction time was 4h, and sampling was taken to observe whether the esterification was complete. If the esterified product is clear and transparent, PBAT co-esterified product is obtained.

[0070] Then the temperature of the esterification reaction kettle I was raised to 235°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly reduced from 80 kPa to 1 kPa within 1 hour, and the vacuum was maintained at 1 kPa for another 1 hour to obtain PBAT oligomers.

[0071] (2) Preparation of PLA oligomers

[0072] Accurately weigh 1.25 kg of lactic acid and 1.5 g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, the molar ratio of stannous octoate to p-toluenesulfonic acid is 2:1) and add them to reactor II for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 185°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually pumped from normal pressure to vacuum 90kpa, and the esterification reaction time is 6h. Take samples to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0073] Then the temperature of the esterification reaction kettle II was raised to 210°C for pre-polycondensation reaction. The vacuum in the kettle was slowly reduced from 90 kPa to 1 kPa within 2 hours, and the vacuum was maintained at 1 kPa for another 2 hours to obtain PLA oligomers.

[0074] (3) Preparation of PBAT+PLA final polymer:

[0075] The PBAT prepolymer, PLA prepolymer (the molar ratio of PBAT prepolymer to PLA prepolymer is 9:1) and catalyst C3 (the molar ratio of tetrabutyl titanate to p-toluenesulfonic acid is 4:1) prepared above were added to the polycondensation reactor III for melt blending, and the polycondensation reaction temperature was controlled to be 235°C, the reaction vacuum was 50 Pa absolute pressure, and the reaction time was 4 h to obtain a completely reacted PBAT-PLA final polymer. After the reaction was completed, the pellets were cut and dried to obtain PBAT-PLA copolyester.

[0076] Example 2.

[0077] The specific steps are as follows:

[0078] (1) Preparation of PBAT oligomers:

[0079] 3.035kg of purified terephthalic acid, 2.89kg of adipic acid, 5.486kg of 1,4-butanediol and 16g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 6.4:1) were accurately weighed and added to reactor I for esterification reaction. The esterification reactor was heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 230°C. The stirring speed of the reactor was gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure was gradually pumped from normal pressure to vacuum 80kpa, and the esterification reaction time was 4h. Samples were taken to observe whether the esterification was complete. If the esterified product was clear and transparent, PBAT co-esterified product was obtained.

[0080] Then the temperature of the esterification reaction kettle I was raised to 235°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly reduced from 80 kPa to 1 kPa within 1 hour, and the vacuum was maintained at 1 kPa for another 1 hour to obtain PBAT oligomers.

[0081] (2) Preparation of PLA oligomers

[0082] Accurately weigh 2.5 kg of lactic acid and 3 g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 2:1) and add them into reactor II for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 185°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually evacuated from normal pressure to vacuum 90kpa. The esterification reaction time is 6h. Samples are taken to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0083] Then the temperature of the esterification reaction kettle II was raised to 210°C for pre-polycondensation reaction. The vacuum in the kettle was slowly reduced from 90 kPa to 1 kPa within 2 hours, and the vacuum was maintained at 1 kPa for another 2 hours to obtain PLA oligomers.

[0084] (3) Preparation of PBAT+PLA final polymer:

[0085] The above-mentioned PBAT prepolymer and PLA prepolymer (the molar ratio of PBAT prepolymer to PLA prepolymer is 8:2) and catalyst C3 (the molar ratio of tetrabutyl titanate to p-toluenesulfonic acid is 4:1) 5g are added to the polycondensation reactor III for melt blending, the polycondensation reaction temperature is controlled to be 235°C, the reaction vacuum is 50pa absolute pressure, the reaction time is 4h, and a completely reacted PBAT-PLA final polymer is obtained. After the reaction is completed, the pellets are cut and dried to obtain PBAT-PLA copolyester.

[0086] Example 3.

[0087] The specific steps are as follows:

[0088] (1) Preparation of PBAT oligomers:

[0089] 2.656kg of purified terephthalic acid, 2.53kg of adipic acid, 4.8kg of 1,4-butanediol and 14g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 6.4:1) were accurately weighed and added to reactor I for esterification reaction. The esterification reactor was heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 230°C. The stirring speed of the reactor was gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure was gradually pumped from normal pressure to vacuum 80kpa, and the esterification reaction time was 4h. Samples were taken to observe whether the esterification was complete. If the esterified product was clear and transparent, PBAT co-esterified product was obtained.

[0090] Then the temperature of the esterification reaction kettle I was raised to 235°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly reduced from 80 kPa to 1 kPa within 1 hour, and the vacuum was maintained at 1 kPa for another 1 hour to obtain PBAT oligomers.

[0091] (2) Preparation of PLA oligomers

[0092] Accurately weigh 3.75 kg of lactic acid and 4.5 g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate and p-toluenesulfonic acid is 2:1) and add them into reactor II for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 185°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually evacuated from normal pressure to vacuum 90kpa. The esterification reaction time is 6h. Samples are taken to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0093] Then the temperature of the esterification reaction kettle II was raised to 210°C for pre-polycondensation reaction. The vacuum in the kettle was slowly reduced from 90 kPa to 1 kPa within 2 hours, and the vacuum was maintained at 1 kPa for another 2 hours to obtain PLA oligomers.

[0094] (3) Preparation of PBAT+PLA final polymer:

[0095] The above-mentioned PBAT prepolymer and PLA prepolymer (the molar ratio of PBAT prepolymer to PLA prepolymer is 7:3) and catalyst C3 (the molar ratio of tetrabutyl titanate to p-toluenesulfonic acid is 4:1) 5g are added to the polycondensation reactor III for melt blending, the polycondensation reaction temperature is controlled to be 235°C, the reaction vacuum is 50pa absolute pressure, the reaction time is 4h, and a completely reacted PBAT-PLA final polymer is obtained. After the reaction is completed, the pellets are cut and dried to obtain PBAT-PLA copolyester.

[0096] Example 4.

[0097] The specific steps are as follows:

[0098] (1) Preparation of PBAT oligomers:

[0099] 2.276kg of purified terephthalic acid, 2.17kg of adipic acid, 4.12kg of 1,4-butanediol and 12g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 6.4:1) were accurately weighed and added to reactor I for esterification reaction. The esterification reactor was heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 230°C. The stirring speed of the reactor was gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure was gradually pumped from normal pressure to vacuum 80kpa, and the esterification reaction time was 4h. Samples were taken to observe whether the esterification was complete. If the esterified product was clear and transparent, PBAT co-esterified product was obtained.

[0100] Then the temperature of the esterification reaction kettle I was raised to 235°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly reduced from 80 kPa to 1 kPa within 1 hour, and the vacuum was maintained at 1 kPa for another 1 hour to obtain PBAT oligomers.

[0101] (2) Preparation of PLA oligomers

[0102] Accurately weigh 5kg of lactic acid and 6g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 2:1) and add them into reactor II for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 185°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually evacuated from normal pressure to vacuum 90kpa. The esterification reaction time is 6h. Samples are taken to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0103] Then the temperature of the esterification reaction kettle II was raised to 210°C for pre-polycondensation reaction. The vacuum in the kettle was slowly reduced from 90 kPa to 1 kPa within 2 hours, and the vacuum was maintained at 1 kPa for another 2 hours to obtain PLA oligomers.

[0104] (3) Preparation of PBAT+PLA final polymer:

[0105] The above-mentioned PBAT prepolymer and PLA prepolymer (the molar ratio of PBAT prepolymer to PLA prepolymer is 6:4) and catalyst C3 (the molar ratio of tetrabutyl titanate to p-toluenesulfonic acid is 6:4) 5g are added to the polycondensation reactor III for melt blending, the polycondensation reaction temperature is controlled to be 235°C, the reaction vacuum is 50pa absolute pressure, the reaction time is 4h, and a completely reacted PBAT-PLA final polymer is obtained. After the reaction is completed, the pellets are cut and dried to obtain PBAT-PLA copolyester.

[0106] Example 5.

[0107] The specific steps are as follows:

[0108] (1) Preparation of PBAT oligomers:

[0109] 1.897kg of purified terephthalic acid, 1.81kg of adipic acid, 3.43kg of 1,4-butanediol and 10g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 6.4:1) were accurately weighed and added to reactor I for esterification reaction. The esterification reactor was heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 230°C. The stirring speed of the reactor was gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure was gradually pumped from normal pressure to vacuum 80kpa, and the esterification reaction time was 4h. Samples were taken to observe whether the esterification was complete. If the esterified product was clear and transparent, PBAT co-esterified product was obtained.

[0110] Then the temperature of the esterification reaction kettle I was raised to 235°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly reduced from 80 kPa to 1 kPa within 1 hour, and the vacuum was maintained at 1 kPa for another 1 hour to obtain PBAT oligomers.

[0111] (2) Preparation of PLA oligomers

[0112] Accurately weigh 6.25 kg of lactic acid and 7.5 g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 2:1) and add them into reactor II for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 185°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually evacuated from normal pressure to vacuum 90kpa. The esterification reaction time is 6h. Samples are taken to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0113] Then the temperature of the esterification reaction kettle II was raised to 210°C for pre-polycondensation reaction. The vacuum in the kettle was slowly reduced from 90 kPa to 1 kPa within 2 hours, and the vacuum was maintained at 1 kPa for another 2 hours to obtain PLA oligomers.

[0114] (3) Preparation of PBAT+PLA final polymer:

[0115] The above PBAT prepolymer and PLA prepolymer (the molar ratio of tetrabutyl titanate and p-toluenesulfonic acid is 5:5) and catalyst C3 (the molar ratio of tetrabutyl titanate and p-toluenesulfonic acid is 4:1) 5g were added to the polycondensation reactor III for melt blending, the polycondensation reaction temperature was controlled to 235°C, the reaction vacuum was 50pa absolute pressure, the reaction time was 4h, and a completely reacted PBAT-PLA final polymer was obtained. After the reaction was completed, the pellets were cut and dried to obtain PBAT-PLA copolyester.

[0116] Comparative Example 1: Preparation of PBAT

[0117] The specific steps are as follows:

[0118] Accurately weigh 3.794kg of purified terephthalic acid, 3.615kg of adipic acid, 6.86kg of 1,4-butanediol, and 20g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 6.4:1) and add them to the reactor for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 230°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a rate of 10HZ / min. The esterification reaction pressure is gradually pumped from normal pressure to vacuum 80kpa, and the esterification reaction time is 4h. Take a sample to observe whether the esterification is complete. If the esterified product is clear and transparent, the PBAT co-esterified product is obtained.

[0119] Then the temperature of the esterification reaction kettle I was raised to 235°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly reduced from 80 kPa to 1 kPa within 1 hour, and the vacuum was maintained for 1 hour to obtain PBAT oligomers.

[0120] The polycondensation temperature was continuously controlled at 235°C, the reaction vacuum was controlled at an absolute pressure of 50 kPa, and the reaction time was 4 hours to obtain a completely reacted PBAT final polymer. After the reaction was completed, the pellets were cut and dried to obtain PBAT copolyester.

[0121] Comparative Example 2: Preparation of PLA

[0122] The specific steps are as follows:

[0123] Accurately weigh 12.5kg of lactic acid and 15g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, the molar ratio of stannous octoate and p-toluenesulfonic acid is 2:1) and add them to the reactor for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5℃ / min, and gradually heated to the esterification reaction temperature of 185℃. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually pumped from normal pressure to vacuum 90kpa, and the esterification reaction time is 6h. Take samples to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0124] Then the temperature of the esterification reaction kettle II was raised to 210°C for pre-polycondensation reaction. The vacuum in the kettle was slowly reduced from 90 kPa to 1 kPa within 2 hours, and the vacuum was maintained for another 2 hours to obtain PLA oligomers.

[0125] The polycondensation temperature was continuously controlled at 210°C, the reaction vacuum was controlled at an absolute pressure of 50 kPa, and the reaction time was 4 hours to obtain a completely reacted PLA final polymer. After the reaction was completed, the pellets were cut and dried to obtain a PLA resin.

[0126] Example 6.

[0127] The viscosity, hue, melt index, melting point, carboxyl group, mechanical properties and other related indicators of the polyester products of Examples 1-5 and Comparative Examples 1-2 were tested.

[0128] The intrinsic viscosity, hue melt index, melting point, carboxyl group, mechanical properties and other related indicators of polyester are measured by the following methods:

[0129] Intrinsic viscosity: Phenol-tetrachloroethane mixture is used as solvent and measured with Ubbelohde viscometer at 25°C;

[0130] Hue: After the pellet sample was treated at 135°C for 1 hour, its Hunter L value (brightness), a value (red-green hue) and b value (yellow-blue hue) were measured using a BYK Gardner color-view automatic colorimeter. The higher the L value, the greater the brightness; the higher the b value, the yellower the polyester chips. For the present invention, it is desirable to pursue a high L value and a low b value;

[0131] Melt index: measured at 250°C and 2.16 kg using an Instron CEAST MF20 melt flow rate tester.

[0132] Melting point: measured using Shimadzu DSC-60Plus differential scanning calorimeter at a heating rate of 20°C / min.

[0133] Carboxyl: Use o-cresol / chloroform as mixed solvent in a mass ratio of 7:3 and potassium hydroxide-benzyl alcohol as titrant and determine by volumetric titration.

[0134] Mechanical properties: The specimens were molded into Type IA strips by an injection molding machine. The tensile strength and elongation at break were tested at a tensile speed of 50 mm / min. The cantilever beam notch impact test was performed by cutting a right-angle notch on the strips.

[0135] The test results are shown in Table 1.

[0136] Table 1

[0137]

[0138] As shown in Table 1, the PBAT-PLA copolyester successfully prepared by copolymerization in the present invention has excellent mechanical properties, lower carboxyl groups, better product compatibility, more uniform molecular weight distribution, and better processing performance. When the weight ratio of PBAT prepolymer to PLA prepolymer is 9-1:1, this ratio helps to improve the performance of the copolyester.

[0139] Example 7.

[0140] The specific steps are as follows:

[0141] (1) Preparation of PBAT oligomers:

[0142] 1.778kg of refined terephthalic acid, 1.70kg of adipic acid, 3.43kg of 1,4-butanediol (the molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1.5:1, and the molar ratio of terephthalic acid and adipic acid is 48:52) and 10g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 6:1) are accurately weighed and added to reactor I for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5℃ / min, and gradually heated to the esterification reaction temperature of 225℃. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually pumped from normal pressure to vacuum 85kpa, and the esterification reaction time is 5h. Samples are taken to observe whether the esterification is complete. If the esterified product is clear and transparent, PBAT co-esterified product is obtained.

[0143] Then the temperature of the esterification reaction kettle I was raised to 230°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly reduced from 85 kPa to 2 kPa within 1 hour, and the vacuum was maintained at 2 kPa for 1.5 hours to obtain PBAT oligomers;

[0144] (2) Preparation of PLA oligomers

[0145] Accurately weigh 6.25 kg of lactic acid and 8.0 g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, the molar ratio of stannous octoate and p-toluenesulfonic acid is 1.5:1) and add them into reactor II for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 180°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually evacuated from normal pressure to vacuum 95kpa. The esterification reaction time is 8h. Samples are taken to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0146] Then the temperature of the esterification reactor II was raised to 200°C for pre-polycondensation reaction. The vacuum in the reactor was slowly reduced from 95 kPa to 2 kPa within 2 hours, and the vacuum was maintained at 2 kPa for 3 hours to obtain PLA oligomers.

[0147] (3) Preparation of PBAT+PLA final polymer:

[0148] The PBAT prepolymer prepared above was mixed with the PLA prepolymer in a molar ratio of 1:1, and 5 g of catalyst C3 (the molar ratio of tetrabutyl titanate and p-toluenesulfonic acid was 3:1) was added to the polycondensation reactor III for melt blending. The polycondensation reaction temperature was controlled to be 230° C., the reaction vacuum was 5 Pa absolute pressure, and the reaction time was 5 h to obtain a completely reacted PBAT-PLA final polymer. After the reaction was completed, the pellets were cut and dried to obtain PBAT-PLA copolyester.

[0149] Example 8.

[0150] The specific steps are as follows:

[0151] (1) Preparation of PBAT oligomers:

[0152] 2.016kg of refined terephthalic acid, 1.92kg of adipic acid, 3.43kg of 1,4-butanediol (the molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1.7:1, and the molar ratio of terephthalic acid and adipic acid is 48:52) and 10g of catalyst C1 (the molar ratio of tetrabutyl titanate and triphenyl phosphate is 7:1) were accurately weighed and added to reactor I for esterification reaction. The esterification reactor was heated by heat transfer oil at a heating rate of 5℃ / min, and gradually heated to the esterification reaction temperature of 245℃. The stirring speed of the reactor was gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure was gradually pumped from normal pressure to vacuum 75kpa, and the esterification reaction time was 3h. Samples were taken to observe whether the esterification was complete. If the esterified product was clear and transparent, PBAT co-esterified product was obtained.

[0153] Then, the temperature of the esterification reaction kettle I was raised to 225°C for pre-polycondensation reaction, and the vacuum in the kettle was slowly pumped from 75 kPa to 1 kPa within 1 hour, and the vacuum was maintained at 1 kPa for another 1 hour to obtain PBAT oligomers;

[0154] (2) Preparation of PLA oligomers

[0155] Accurately weigh 6.25 kg of lactic acid and 7.5 g of catalyst C2 (including stannous octoate, p-toluenesulfonic acid and polyethylene glycol, the molar ratio of stannous octoate and p-toluenesulfonic acid is 2.5:1) and add them into reactor II for esterification reaction. The esterification reactor is heated by heat transfer oil at a heating rate of 5°C / min, and gradually heated to the esterification reaction temperature of 190°C. The stirring speed of the reactor is gradually increased from 0HZ to 50HZ at a speed of 10HZ / min. The esterification reaction pressure is gradually evacuated from normal pressure to vacuum 85kpa. The esterification reaction time is 5h. Samples are taken to observe whether the esterification is complete. If the esterified product is clear and transparent, PLA esterified product is obtained.

[0156] Then the temperature of the esterification reactor II was raised to 220°C for pre-polycondensation reaction. The vacuum in the reactor was slowly reduced from 85 kPa to 3 kPa within 2 hours, and the vacuum was maintained at 3 kPa for 1 hour to obtain PLA oligomers.

[0157] (3) Preparation of PBAT+PLA final polymer:

[0158] The PBAT prepolymer prepared above was mixed with the PLA prepolymer in a molar ratio of 1:1, and 5 g of catalyst C3 (the molar ratio of tetrabutyl titanate and p-toluenesulfonic acid was 5:1) was added to the polycondensation reactor III for melt blending. The polycondensation reaction temperature was controlled to be 225°C, the reaction vacuum was 45 Pa absolute pressure, and the reaction time was 3 h to obtain a completely reacted PBAT-PLA final polymer. After the reaction was completed, the pellets were cut and dried to obtain PBAT-PLA copolyester.

[0159] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.

Claims

1. A method for preparing PBAT-PLA copolyester, characterized in that: The following steps are involved: Preparation of PBAT copolyester oligomer: terephthalic acid, adipic acid, 1,4-butanediol and catalyst 1 are mixed and subjected to esterification reaction to obtain PBAT coesterification product; the PBAT coesterification product is subjected to pre-polycondensation reaction to obtain PBAT prepolymer, i.e., the PBAT copolyester oligomer; Preparation of PLA resin oligomer: Lactic acid and catalyst 2 are mixed and subjected to esterification reaction to obtain PLA ester; the PLA ester is subjected to pre-polycondensation reaction to obtain PLA prepolymer, i.e., the PLA resin oligomer; Preparation of final polymer: After the PBAT prepolymer and the PLA prepolymer are melt-blended, catalyst 3 is added to carry out polycondensation reaction to obtain a PBAT-PLA final polymer, namely, the PBAT-PLA copolyester.

2. The preparation method according to claim 1, characterized in that: In the preparation of the PBAT copolyester oligomer, the esterification reaction temperature is 225-245°C, the time is 3-5h, and the pressure is 75-85kpa; The pre-polycondensation reaction temperature is 225-235°C, the time is 2-2.5h, and the pressure is 1-2kpa; The molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1:15-1.

7.

3. The preparation method according to claim 2, characterized in that: In the preparation of the PBAT copolyester oligomer, the esterification reaction temperature is 230° C., the time is 4 h, and the pressure is 80 kPa; The pre-polycondensation reaction temperature is 235°C, the time is 2h, and the pressure is 1kpa; The molar ratio of terephthalic acid, adipic acid and 1,4-butanediol is 1:1.6, and the molar ratio of terephthalic acid and adipic acid is 48:

52.

4. The preparation method according to claim 1, characterized in that: In the preparation of PLA resin oligomer, the esterification reaction temperature is 180-190°C, the time is 5-8h, and the pressure is 85-95kpa; The pre-polycondensation reaction temperature is 200-220°C, the time is 3-5h, and the pressure is 1-3kpa.

5. The preparation method according to claim 4, characterized in that: In the preparation of PLA resin oligomer, the esterification reaction temperature is 185°C, the time is 6h, and the pressure is 90kpa; The pre-polycondensation reaction temperature is 210°C, the time is 4 hours, and the pressure is 1 kPa.

6. The preparation method according to claim 1, characterized in that: In the preparation of the final polymer, the polycondensation reaction is carried out under nitrogen protection, the polycondensation reaction temperature is 225-235°C, the time is 3-5h, and the pressure is 5-50pa absolute pressure; The molar ratio of PBAT prepolymer to PLA prepolymer is 9-1:

1.

7. The preparation method according to claim 6, characterized in that: In the preparation of the final polymer, the polycondensation reaction temperature is 235° C., the time is 4 hours, and the pressure is 50 Pa absolute pressure.

8. The preparation method according to claim 1, characterized in that: The molar ratio of tetrabutyl titanate to triphenyl phosphate in the catalyst 1 is 6-7:1; The catalyst 2 comprises stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 1.5-2.5:1; The molar ratio of tetrabutyl titanate to p-toluenesulfonic acid in the catalyst 3 is 3-5:

1.

9. The preparation method according to claim 8, characterized in that: The molar ratio of tetrabutyl titanate to triphenyl phosphate in the catalyst 1 is 6.4:1; The catalyst 2 comprises stannous octoate, p-toluenesulfonic acid and polyethylene glycol, and the molar ratio of stannous octoate to p-toluenesulfonic acid is 2:1; The molar ratio of tetrabutyl titanate to p-toluenesulfonic acid in the catalyst 3 is 4:

1.

10. A PBAT-PLA copolyester, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method of tertiary amine modified polyester capable of being rapidly degraded

    CN120118299B